The family health strategy and the programmatic vulnerability in assistance to hiv/aids: a literature survey - de Souza Silva, José Augusto; Ferreira do Val, Luciane; Yasuko Izumi Nichiata, Lucia (O Mundo da Saúde, 2010)
The study aimed to analyze in published literature the potentialities and difficulties of Family Health Strategy (ESF) regarding the Programmatic Vulnerability in assistance to HIV/AIDS. This is a narrative survey of publications in the period January-July 2009 in the databases LILACS, MEDLINE, ScIELO, PeriEnf and Teses USP. We selected 16 texts that were grouped, analyzed and prioritized in Structure and Dynamics of Services Organization (access to services and resources, qualification of professionals, ESF team internal organization and with other services) and Actions Implementation (early diagnosis, counseling, educative groups and home visits). Although there are challenges, ESF has contributed in important ways to the reduction of Programmatic Vulnerability to HIV/AIDS.